Hubungan Kompetensi Manajerial Kepala Sekolah Dalam Meningkatkan Kinerja Guru SLB Negeri Sasa Kota Ternate - Sahnaz Hi. Ahmad; Said Hasan; Ade Haerullah (Pusat Riset dan Inovasi Nasional, 2023)
Managerial competence will determine the progress of an educational institution. If the principal's managerial competence is good, it will be able to improve teacher performance. This study aims to describe the relationship between principal managerial competency and teacher performance improvement. The method used in this study is to use a qualitative approach. This research was conducted at SLB Negeri Sasa Ternate City. The subjects in this study were school principals and teachers. Data collection techniques were carried out in natural settings (natural conditions), primary data sources, and data collection techniques involved participant observation, in-depth interviews and documentation. The results of this study indicate that the head of SLB Negeri Sasa Kota Ternate is able to optimize school resources, both teachers and staff, direct students to be role models and take full responsibility for school progress. Patience, caring, hardworking, punctual attitude. The principal tries to establish himself as a leader according to the expectations of the teachers and all parties. So that it can be said that the principal already has a management program to improve teacher performance. The performance of a good teacher does not just happen, there are many factors that affect the high and low performance of a teacher, including internal factors and external factors, internal factors depend on the skills of the teacher himself, while external factors influence a lot, one of which is the principal's leadership competence. . This shows that the managerial principal can provide a positive increase in teacher performance.